War for memory: Malvinas and the clash among veterans, military and civilians, and relatives of soldiers killed in the field of memory construction: Guerra pela memória: Malvinas e o embate entre veteranos (militares e civis) e familiares de soldados mortos no campo da construção de memórias (Revista de História da UEG (REVHIST), 2022)
We start the article by analyzing the conflicting field of constructing memories on traumatic events that marked History. Afterwards, we focus on how this conflict takes place in the construction of memories about the Malvinas War, which involve various sectors of Argentine society, mainly veterans of war, military and civilians, and relatives of fallen soldiers. The analyzed period starts in 1982, with the end of the war, and ends in 2015, the year of conclusion of the research. When analyzing the vast Argentine bibliographic material on the subject and interviewing veterans and family members of soldiers who died in the conflict, we concluded that the main factor in the conflict in the construction of memories of the war is that it was undertaken by a government of a military dictatorship, which, for a group, is an aspect that should always be remembered due to the abuses committed by officers against conscripts in the front, and, for others, should be forgotten to avoid arguments that delegitimize the war.Keywords: Constructions of memories. Malvinas War. Argentine Military Dictatorship.